Optimalisasi Program Tahfidz Al-Qur'an: Analisis Implementasi dan Hambatan di SMP Muhammadiyah Al-Kautsar PK Kartasura - Zakiya Salsabillah; Mutohharun Jinan (Instructional Development Journal, 2026)
This research aims to describe the implementation of the tahfidz Al-Qur'an program at SMP Muhammadiyah Al-Kautsar Kartasura Special Program and identify the obstacles faced in the implementation process. This research uses a qualitative approach with a descriptive method. The research informant is a tahfidz teacher who is directly involved in the implementation of the program. Data collection is done through interviews, observations, and documentation. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions, while the validity of data is tested through triangulation techniques. The research results show that tahfidz activities are carried out in a structured manner through independent memorization, muraja'ah, and memorization deposit to the supervising teacher with a schedule of four times per week for 90 minutes each meeting. The school targets the achievement of six juz memorization for three years of study. Memorization evaluation is carried out through monitoring books and tahfidz exams equipped with certain assessment systems. In its implementation, this program faces several obstacles, including differences in students' basic abilities, lack of muraja'ah consistency, time constraints between tahfidz and academic activities, and variations in student learning motivation. In general, the tahfidz program has gone well and contributed to the improvement of students' Al-Qur'an memorization skills